Social determinants of health linked with oral health in a representative sample of U.S. adults - Raghad Obeidat; Lisa J. Heaton; Eric P. Tranby; John O’Malley; Peggy Timothé (BMC Oral Health)
Abstract Background Oral diseases remain a significant public health problem worldwide, with growing gaps in oral health status among various socioeconomic groups. The objective of the current study is to analyze the impact of different social determinants of health (SDOH) on oral health outcomes (frequency of dental visits, self-reported oral health status, embarrassment because of oral health status, and tooth loss) among a representative sample of United States (U.S.) adults. Methods Cross-sectional data for this observational study came from adults aged 18 and above (N = 5,320) participating in the nationally representative 2021 State of Oral Health Equity in America survey. Bivariate and multivariable analyses were conducted to examine the associations between oral health outcomes (dependent variables) and SDOH independent variables: structural (race/ethnicity, income, education); and intermediary (lack of transportation, food insecurity, racial discrimination, and housing instability), controlling for the confounding variables of age, gender, employment status, dental insurance, self-rated mental/emotional health, self-rated physical health, presence of one or more chronic conditions, and having had a routine physical examination in the past year. Results When controlling for confounding variables, Black adults were less likely than White adults to have had a dental visit in the last year (odds ratio (OR) = 0.72 (95% confidence interval (CI) = 0.57–0.92, p < 0.05), more likely to report feeling self-conscious or embarrassed due to their oral health (OR = 1.67 (95% CI = 1.31–2.12, p < 0.05), and more likely to have at least one permanent tooth removed (OR = 1.67 (95% CI = 1.31–2.13, p < 0.05). Higher income and more education were significantly associated with greater odds of rating one’s oral health positively and having had a dental visit in the past year and lesser odds of feeling self-conscious or having at least one tooth removed (p’s < 0.05). All four intermediary determinants were associated with significant (p < 0.05) and negative odds of having a dental visit in the past year and reporting positive oral health, and with positive odds of having at least one permanent tooth removed. The odds of feeling self-conscious or embarrassed due to their oral health were significantly and positive associated with all intermediary determinants except for racial discrimination (OR = 1.21, 95% CI = 1.00–1.46). Conclusions Significant inequities still exist in the U.S. regarding SDOH and their relationship to oral health. Improving oral health will involve addressing SDOH. Successful policy and public health interventions must address not only structural factors but also intermediary SDOH.